Tuberculosis, HIV, and viral hepatitis diagnostics in eastern Europe and central Asia: high time for integrated and people-centred services. Issue 2 (February 2020) - Dara, Masoud; Ehsani, Soudeh; Mozalevskis, Antons; Vovc, Elena; Simões, Daniel; Avellon Calvo, Ana; Casabona i Barbarà, Jordi; Chokoshvili, Otar; Felker, Irina; Hoffner, Sven; Kalmambetova, Gulmira; Noroc, Ecatarina; et al.
Summary: Globally, high rates (and in the WHO European region an increasing prevalence) of co-infection with tuberculosis and HIV and HIV and hepatitis C virus exist. In eastern European and central Asian countries, the tuberculosis, HIV, and viral hepatitis programmes, including diagnostic services, are separate vertical structures. In this Personal View, we consider underlying reasons for the poor integration for these diseases, particularly in the WHO European region, and how to address this with an initial focus on diagnostic services. In part, this low integration has reflected different diagnostic development histories, global funding sources, and sample types used for diagnosis (eg, typically sputum for tuberculosis and blood for HIV and hepatitis C). Cooperation between services improved as patients with tuberculosis needed routine testing for HIV and vice versa, but financial, infection control, and logistical barriers remain. Multidisease diagnostic platforms exist, but to be used optimally, appropriate staff training and sensible understanding of different laboratory and infection control risks needs rapid implementation. Technically these ideas are all feasible. Poor coordination between these vertical systems remains unhelpful. There is a need to increase political and operational integration of diagnostic and treatment services and bring them closer to patients.